Where and what is the PPN and what is its role in locomotion?. (20th April 2015) - Windels, Francois; Thevathasan, Wesley; Silburn, Peter; Sah, Pankaj
Abstract : This scientific commentary refers to 'The integrative role of the pedunculopontine nucleus in human gait', by Lau et al . (doi:10.1093/brain/awv047 ).